AI-enhanced visible light communication systems in body area networks - Shrestha, Shreyash; Attaphongse Taparugssanagorn; Chaklam Silpasuwanchai; Chantri Polprasert; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Visible Light Communication (VLC) is one of the popular topics of interest and research in the field of wireless communications. It basically passes information from the trans mitter to the receiver via light sources such as LED, Laser Diode etc. As the world of wireless technology is increasing with high demand of bandwidth from IoT devices and smart cities, VLC is the pivotal area which needs to be researched. Likewise, as our RF spectrum is congested with the excessive use of RF wireless devices, VLC can act as a new means of communication which can ease out the RF congestion with reliable and efficient communication. In the era of Artificial Intelligence (AI) the use of such models can also help enhance the capability of different wireless devices making the system more robust and flexible in various conditions. As VLC has many advantages implementing such system might need moreanalysis research as it is very easily affected by noises and path-loss in the channel (air). This thesis dives deeper into the signal pro cessing of the VLC system on the transmitter side and receiver side with integration of the hybrid AI model (CNN + Transformer). The signal is passed through modeled VLCchannel and received with further processing by AI model for channel estimation equalization and adaptive bit loading. This work can help in further understanding the working of VLC system and the measures need to make the model more efficient.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Telecommunications
Thesis (M. Eng.) - Asian Institute of Technology, 2025
Keywords: Optical communications; Signal Processing; Artificial Intelligence